Conditional Recognition: The Juridical Gap Between Normative Rights and Implementation Reality for “Indigenous Peoples” in Indonesia - Rambe, Muhammad Juang (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Peoples”-Masyarakat Hukum Adat/MHA in Indonesia, focusing on the gap between normative recognition and implementation reality. The method used is qualitative-descriptive normative legal research, employing statutory, historical, conceptual, comparative, and case approaches focused on Constitutional Court Decision No. 35/PUU-X/2012. The findings indicate that the legal relationship is trapped within a “conditional recognition” paradigm mandated by Article 18B of the 1945 Constitution. Despite significant normative progress, such as the Constitutional Court Decision No. 35/2012, which juridically removed customary forests from the state forest classification, implementation is systemically obstructed. These obstructions manifest in the disharmony of subordinative sectoral laws and the “decentralization of barriers” to regional governments, which require Local Regulations (Perda) that are often stalled by conflicting economic interests and a lack of political will. It is concluded that this fundamental gap is not a mere technical failure but a manifestation of a deep political-economic contestation over resources, perpetuating legal uncertainty for MHA. The implication of this research is the urgent need to pass the Bill on MHA as a primary legal umbrella to standardize criteria and rights protection mechanisms.